STUDI PERILAKU HARIAN ORANGUTAN (Pongo pygmaeus) DI PUSAT REHABILITASI SINTANG ORANGUTAN CENTER HUTAN TEMBAK KABUPATEN SINTANG KALIMANTAN BARAT - Maulana, .; Rifanjani, Slamet; Siahaan, Sarma (Universitas Tanjungpura, 2017)
This research aims to find out about the daily behavior of orangutan in the Sintang Orangutan Rehabilitation Center. The main activities of Sintang Orangutan Center are rescue, rehabilitation, and realease of the animal into is natural habitat. The method used was focal animal sampling or by observing and recording the behavior of one individual during a certain period of time as long as the individual is always visible. Collecting data in this research was focused on the individual orangutan as the object or goal in each observation. Data recording was made every minute on daily behavior as â€œpoint sampleâ€. This method works with semi-solitary orangutans with a character of slow movement. Observations of orangutan behavior were conducted the whole day, from Â wake-up time in the morning (at around 5:00 a.m. to 17:oo PM) until bedtime and did not do activities in the evening (at around 6:00 p.m. to 19:00 pm). The results showed that orangutans use a lot of time for feeding activities, while the minor activities are making a nest. Orangutans targeted in this research used 22.96% of the time daily for motion, 44.48% for eating, 20.78% for taking a rest, 8.29% for social activities, 1.43% for the activity of building nests and 2.03% for other activities. Â Keywords: Behavior, Orangutan, Pongo pygmaeus, Rehabilitation.